In-process measurement - Loxham, J. (College of Aeronautics, 1967)
"I often say that when you can measure what you are speaking about and express it in numbers, you know something about it; when you cannot measure it, when you cannot express it in numbers, your knowledge is of a meagre and unsatisfactory kind." The above statement was made by Lord Kelvin (1824-1907) about''' hundred years ago and is reproduced as the main theme of the present paper. The only qualification that should be made is that when Lord Kelvin made the above statement he did not think that the philosophy he expounded was specially appropriate to engineering manufacture. The present paper will consider how this philosophy can b3 applied to engineering manufacture only. ...[cont.]